2020
DOI: 10.1038/s41467-020-17933-8
|View full text |Cite
|
Sign up to set email alerts
|

Cryo-EM structure of an activated VIP1 receptor-G protein complex revealed by a NanoBiT tethering strategy

Abstract: Vasoactive intestinal polypeptide receptor (VIP1R) is a widely expressed class B G proteincoupled receptor and a drug target for the treatment of neuronal, metabolic, and inflammatory diseases. However, our understanding of its mechanism of action and the potential of drug discovery targeting this receptor is limited by the lack of structural information of VIP1R. Here we report a cryo-electron microscopy structure of human VIP1R bound to PACAP27 and Gs heterotrimer, whose complex assembly is stabilized by a N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
209
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 177 publications
(214 citation statements)
references
References 51 publications
5
209
0
Order By: Relevance
“…We used NanoBiT strategy 22 24 to stabilize the complex, in which GLP-2R was directly attached to LgBiT and rat Gβ was linked to HiBiT with a 15-amino acid linker in between. Transiently transfected HEK 293T cells showed that the C-terminus-truncated GLP-2R(1–490)-LgBiT had a 6-fold stronger interaction with Gβ-SmBiT than the wild-type (WT) receptor(1–553)-LgBiT (Supplementary information, Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We used NanoBiT strategy 22 24 to stabilize the complex, in which GLP-2R was directly attached to LgBiT and rat Gβ was linked to HiBiT with a 15-amino acid linker in between. Transiently transfected HEK 293T cells showed that the C-terminus-truncated GLP-2R(1–490)-LgBiT had a 6-fold stronger interaction with Gβ-SmBiT than the wild-type (WT) receptor(1–553)-LgBiT (Supplementary information, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, we employed cryo-EM to determine the high-resolution structure of the human GLP-2R in complex with G s protein. Based on our prior experience, 22 NanoBiT strategy 23 , 24 was used in this study to stabilize the GLP-2–GLP-2R–G s complex and strengthen the interactions between GLP-2R and Gβ, resulting in a cryo-EM structure at a global resolution of 3.0 Å (Supplementary information, Table S1 ). Our data provide a rational template to facilitate the design of better GLP-2 analogues for therapeutic use and expand our knowledge on the biology of this receptor family.…”
Section: Introductionmentioning
confidence: 99%
“…6d, e ). 9 , 108 The binding of a peptidic ligand causes a conformation rearrangement of the central polar network with simultaneous destabilization of the TM6 helix, thus initiating a sharp kink formation at the conserved motif P 6.47b xxG 6.50b . This central polar network is preserved across the class B receptors solved so far.…”
Section: Gpcr Structurementioning
confidence: 99%
“…G-protein-coupled receptors (GPCRs) are the largest and most diverse group of membrane receptors in eukaryotes and play a role in an incredible array of functions in the human body. 19 …”
Section: Discussionmentioning
confidence: 99%